2013
DOI: 10.3892/or.2013.2269
|View full text |Cite
|
Sign up to set email alerts
|

Role of enolase-1 in response to hypoxia in breast cancer: Exploring the mechanisms of action

Abstract: In the present study, we investigated the effect of reduced enolase-1 expression in human umbilical vein endothelial cells (HUVECs)/MDA-MB-231 cells on the response to hypoxia and the possible mechanisms involved. Breast cancer cells transfected with enolase-1 siRNA were injected into mice to establish a tumor-bearing mouse model, and the correlation between enolase-1 expression and breast cancer angiogenesis, as well as its effect on the efficacy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 27 publications
(27 reference statements)
1
45
0
Order By: Relevance
“…In many tumors, ENO1 promoted the proliferation of cancer cells . Indeed, we observed that ENO1 knockdown reduced the rate of proliferation and capacity of colony formation in MKN‐45 cells and MGC‐803.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In many tumors, ENO1 promoted the proliferation of cancer cells . Indeed, we observed that ENO1 knockdown reduced the rate of proliferation and capacity of colony formation in MKN‐45 cells and MGC‐803.…”
Section: Discussionmentioning
confidence: 69%
“…Within cells, ENO1 is predominantly localized to the cytoplasm. In addition, this protein also has an alternatively translated form that is localized to the nucleus . As a glycolytic enzyme, ENO1 catalyzes the conversion of phosphoenolpyruvate generation from 2‐phosphoglycerate .…”
Section: Introductionmentioning
confidence: 99%
“…α-enolase is a cytosolic glycolytic enzyme and oxidative stress protein. Its expression is elevated in many tumours, including those of the breast, where it is also found on the cell surface [46,47]. The NHE1-α-enolase complex was confirmed by both affinity chromatography and co-immunoprecipitation.…”
Section: Nhe1 and Biosynthetic Proteinsmentioning
confidence: 75%
“…Many reports have demonstrated that ENO1 can be regulated at different levels by multiple factors. For example, ENO1 can be transcriptionally activated by NFκB, 8 HIF-1α 4 and estrogen receptor (ER) α, 2,8 while it also can be downregulated by retinoic acid at the protein level. 39 Moreover, Yu et al 2 observed that estradiol prolongs ENO1 protein half-life and increases ENO1 protein accumulation via a posttranscriptional mechanism.…”
Section: Discussionmentioning
confidence: 99%